UJI AKTIVITAS ANTIBAKTERI EKSTRAK CANGKANG KELAPA SAWIT (Elaeis guineensis Jacq.,) - Haryati, Sri; Hamzah, Faizah; Restuhadi, Fajar (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2015)
The active components of palm oil shell were succesfully extracted by methanol. The methanol extract was, then, subjected to investigate its antibacterial properties. The phytochemical screening demonstrated the presence of triterpenoid and flavonoid compounds. The methanol extract was also tested for antibacterial activity against Staphylococcus aureus (Gram positive bacteria) and Escherichia coli (Gram negative bacteria). The triterpenoid and flavonoid compounds are more sensitive in inhibiting the growth of Gram positive bacteria (Staphylococcus aureus) than Gram negative bacteria (Escherichia coli). Further, the concentration of the methanol extract (1%, 5%, 10%, 25%, 50%, 75% and 100%, respectively), were tested against the Staphylococcus aureus and Escherichia coli. Inhibition zone was formed starting at a concentration of 5% and above, while the largest inhibition zone was at a concentration of 100%, as expected. Minimum Inhibition Concentration (MIC) and Minimum Bactericidal Concentration (MBC) tests were performed by the method of dilution with concentration of 2%, 4%, 6%, 8%, 10%, 12%, 14%, 16%, 18% and 20%, respectively. The methanol extract was as effective as bacteriostatic (according to MIC test) against Staphylococcus aureus and Escherichia coli at concentration 6% and is also considered effective as bactericidal (according to MBC test) at concentration 14% and 12%, respectively.   Keywords: Methanol extract of palm oil shell, Antibacterial, Staphylococus aureus, Escherichia coli